Tablets from Sippar 2 - Leichty, Erle (1987)
xiii-xv: Theophilus Pinches, art. Rassam, Hormuzd (1826-1910), reprinted from the 2nd Suppl. of the Dictionary of National Biography, vol. III 158-161, published in 1912.